2018
DOI: 10.1016/j.ihj.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Coronary angioplasty in spontaneous coronary artery dissection—Strategy and outcomes

Abstract: Objective To study the clinical, angiographic and technical characteristics of patients with spontaneous coronary artery dissection (SCAD) undergoing percutaneous coronary intervention (PCI). Methods This was a retrospective single center study where patients with angiographically confirmed SCAD undergoing PCI over a period of 4 years (2013–2017) were analyzed. We also sought to identify the clinical and angiographic predictors of procedural failure during PCI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The use of cutting balloons to decompress IMH and restore flow has been well described, but this strategy has been largely adopted prior to drug-eluting stent placement. [ 5 7 ] We demonstrate the ability for this technology to improve coronary flow in extensive SCAD as a bridge to cardiac surgery. It is vital that imaging be used in such cases to confirm luminal placement of coronary wires and assess the extent of dissection/haematoma.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The use of cutting balloons to decompress IMH and restore flow has been well described, but this strategy has been largely adopted prior to drug-eluting stent placement. [ 5 7 ] We demonstrate the ability for this technology to improve coronary flow in extensive SCAD as a bridge to cardiac surgery. It is vital that imaging be used in such cases to confirm luminal placement of coronary wires and assess the extent of dissection/haematoma.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have demonstrated a 71.4% success rate of such techniques and reserving escalation to hydrophilic wires for cases in which luminal guidewire placement is not possible. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…Forced and intense injection of the contrast medium must be avoided. (4,5) Although rare, iatrogenic retrograde extension of the dissection into the ascending aorta (0,02 -0,6% of diagnostic and interventional percutaneous procedures) is reported. (6) Dunning et al have found a significantly increased rate in aortocoronary dissections in procedures performed for acute myocardial infarction (AMI) (0,19%) compared with non-AMI cases (0,01%).…”
Section: Percutaneous Coronary Intervention (Pci) In Scad Patients Is Associated With High Rates Of Complicationsmentioning
confidence: 99%
“…In the acute setting, the stent may appear to be well-apposed to the wall but in time as the dissection heals and the hemorrhage resorbs, the stent may well be significantly undersized and malapposed, which predisposes the patient towards repeat revascularization and other catastrophic outcomes like stent thrombosis and its attendant complications. Strategies for successful percutaneous intervention in SCAD patients have been described and include interventional wires selection strategies [ 25 ], use of OCT imaging identify and seal the dissection flap with spot stenting [ 26 ], a multistent strategy with IVUS guidance to place stents proximal and distal to the lesion to prevent medial hemorrhage propagation [ 27 ]. Detailed technical recommendations of PCI techniques to mitigate risk of failure are beyond the scope of this review.…”
Section: Acute Treatment Optionsmentioning
confidence: 99%